2006
DOI: 10.1080/14622200600789585
|View full text |Cite
|
Sign up to set email alerts
|

Clinical laboratory evaluation of potential reduced exposure products for smokers

Abstract: Smoking-related cancer and other disease account for more than 400,000 U.S. deaths annually. Smoking cessation reduces smoking-related disease rates, but relapse rates are high. Thus, interest in reducing the harm of continued smoking is growing. Potential reduced exposure products (PREPs) are marketed to reduce smokers' exposure to smoke toxicants such as carbon monoxide (CO) and carcinogens and may be harm reduction tools. New PREPs are proliferating, but past experience with "low-yield" cigarettes that fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
120
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 28 publications
2
120
0
1
Order By: Relevance
“…Extant research suggests that a single waterpipe use episode can increase blood nicotine levels well beyond those observed after a single cigarette (e.g., over 50 ng/ml for waterpipe, Shafagoj et al, 2002; as compared with approximately 6 ng/ml for a cigarette, Breland et al, 2006). However, 79% of U.S. respondents considered waterpipe less addictive than cigarettes, and most respondents reported not being hooked and having no intention to quit.…”
Section: Discussionmentioning
confidence: 99%
“…Extant research suggests that a single waterpipe use episode can increase blood nicotine levels well beyond those observed after a single cigarette (e.g., over 50 ng/ml for waterpipe, Shafagoj et al, 2002; as compared with approximately 6 ng/ml for a cigarette, Breland et al, 2006). However, 79% of U.S. respondents considered waterpipe less addictive than cigarettes, and most respondents reported not being hooked and having no intention to quit.…”
Section: Discussionmentioning
confidence: 99%
“…While some PREPs for smokers involve tobacco combustion (e.g., Breland, Kleykamp, & Eissenberg, 2006), others involve orally administered noncombustible tobacco products. For example, Star Scientific markets Ariva, a compressed tobacco tablet intended for "adult smokers in situations where they cannot or choose not to smoke."…”
mentioning
confidence: 99%
“…In one study, when use of Advance over 5 days was compared with usual-brand cigarettes (N=12), a significant reduction was observed for urinary total NNAL (51%) with no significant reductions in cotinine and a slight but significant reduction in CO levels (Breland, Acosta, & Eissenberg, 2003). In a more recent within-subject, 5-day study with Advance (N=35), a significant reduction was observed in the Advance condition for urinary total NNAL (37%) compared with own-brand cigarettes, but no differences were observed in 1-HOP, cotinine, or alveolar CO levels at day five (Breland, Kleykamp, & Eissenberg, 2006). In summary, the results from these studies show modest reductions in exposure to one of the tobacco-specific nitrosamines.…”
Section: Methods and Mechanismsmentioning
confidence: 85%
“…Studies also have shown no changes in other biomarkers such as peripheral blood measures (e.g., fibrinogen, hemoglobin, platelets), lung function, pulmonary epithelial permeability (unlike the Stewart et al [2006] findings), vital signs (Frampton et al, 2000;Rennard et al, 2002) or total NNAL and 1-HOP concentrations (Breland et al, 2006). Increases have been observed for CO exposure when using Eclipse (Breland et al, 2006;Frampton et al, 2000;Rennard et al, 2002;Stewart et al, 2006) and for some of the biomarkers for inflammation and oxidative stress (Stewart et al, 2006). Eclipse also has been examined when used in conjunction with cigarettes (Fagerström, Hughes, & Callas, 2002;Fagerström, Hughes, Rasmussen, & Callas, 2000), which may be more reflective of the naturalistic use of this product.…”
Section: Methods and Mechanismsmentioning
confidence: 97%
See 1 more Smart Citation